SENI BAHASA PEREMPUAN: IDEOLOGI DI BALIK WACANA - I Gede Mudana; Ni Wayan Ardini (Soshum: Jurnal Sosial dan Humaniora, 2013)
Behind language, including women’s language, there is an ideology that works in it. From the aspect of how the ideology works and the language relates to the system of power, critical cultural studies will be helpful to explain such a phenomenon, as a discourse, because it assumes the dominance of male power over women. Moreover, it is a discipline which holds that there is no objective, neutral knowledge (including language). This article is a literature review to deconstruct ideology that works behind it according to the paradigm of cultural studies itself.